2019
DOI: 10.21037/cdt.2018.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Racial and sex disparities in resource utilization and outcomes of multi-vessel percutaneous coronary interventions (a 5-year nationwide evaluation in the United States)

Abstract: Background: There is a paucity of data regarding the racial and sex disparities in the outcomes of multivessel percutaneous coronary interventions (MVPCI).Methods: The National Inpatient Sample (NIS) was examined for the years 2010 to 2014 to incorporate adult MVPCI-related hospitalizations using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) procedure codes. We excluded patients with the missing race or gender data from the final scrutiny. Discharge weights were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
2
21
1
1
Order By: Relevance
“…Between varieties of different hospital admission causes, the black race has historically been associated with lower resource utilization and higher in-hospital mortality [10][11][12][20][21][22]. However, among frail patients in our study, the white race was the strongest racial predictor of inpatient mortality.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Between varieties of different hospital admission causes, the black race has historically been associated with lower resource utilization and higher in-hospital mortality [10][11][12][20][21][22]. However, among frail patients in our study, the white race was the strongest racial predictor of inpatient mortality.…”
Section: Discussioncontrasting
confidence: 49%
“…There is a high incidence of post-procedural complications in older patients undergoing cardiovascular interventions, which may be due to a higher number of comorbidities, recurrent multivessel diseases, and or disparities in resource utilization [9][10][11][12]. Moreover, frailty reduces the abilities of stress management, thereby accentuating patients' suffering [13].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence of the impact of race/ethnicity in post-PCI mortality is limited. A study of 769,502 multi-vessel PCI-related hospitalizations found racial disparities with non-whites having lower resource utilization and a greater increase in all-cause mortality post-PCI than whites [ 24 ]. Another study observed that there was no impact of race/ethnicity on the incidence of acute and one-year post-PCI adverse outcomes despite differences in patient demographics, clinical presentation, angiographic characteristics, and treatment strategies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline demographics, hospital characteristics, medical comorbidities, and complication rates were compared between the AF+ and AF-groups. Patient-level sociodemographic and hospitallevel attributes were directly drawn out as provided, whereas the AHRQ comorbidity indicators were employed to identify on admission comorbid disorders using apposite ICD-9 CM codes as detailed earlier [13,14] . We queried the AMICS cases for in-hospital complications using the validated diagnostic codes present among the secondary diagnoses fields (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%